2022
DOI: 10.1101/2022.07.07.22277353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the impact of SARS-CoV-2 lineages and mutations on patient survival

Abstract: After more than two years of COVID-19 pandemic, SARS-CoV-2 still remains a global public health problem. Successive waves of infection have produced new SARS-CoV-2 variants with new mutations whose impact on COVID-19 severity and patient survival is uncertain. A total of 764 SARS-CoV-2 genomes sequenced from COVID-19 patients, hospitalized from 19th February 2020 to 30st April 2021, along with their clinical data, were used for survival analysis. A significant association of B.1.1.7, the alpha lineage, with pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Parallel mutations in multiple independent lineages and variants have been observed (Dorp et al 2020), which may indicate convergent evolution, and are of particular interest in the context of adaptation of SARS-CoV-2 to the human host. Survival analysis of mutations in the SARS-CoV-2 genome revealed 27 of them were significantly associated with higher mortality of patients (Loucera et al 2022). Other authors have reported some sites under positive pressure in the nucleocapsid and spike genes (Benvenuto et al 2020).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Parallel mutations in multiple independent lineages and variants have been observed (Dorp et al 2020), which may indicate convergent evolution, and are of particular interest in the context of adaptation of SARS-CoV-2 to the human host. Survival analysis of mutations in the SARS-CoV-2 genome revealed 27 of them were significantly associated with higher mortality of patients (Loucera et al 2022). Other authors have reported some sites under positive pressure in the nucleocapsid and spike genes (Benvenuto et al 2020).…”
Section: Introductionmentioning
confidence: 97%
“…2020), such as mutations giving rise to epitope loss and antibody escape mechanisms. These have mainly been found in evolved variants isolated from Europe and the Americas, and have critical implications for SARS-CoV-2 fitness (transmission, pathogenesis, and immune interventions (Gupta & Mandal 2020; Loucera et al . 2022)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations